Consumer satisfaction in three dimensions: analysis of the effect of consumer perceived value on shoes, mobile phones, and cars - Aditya Yudanegara (Institute of Computer Science (IOCS), 2023)
This groundbreaking study delves into the captivating realm of 'consumer perceived value' and its profound impact on consumer satisfaction, particularly within the realm of enduring products such as shoes, mobile phones, and cars. We meticulously explore four facets of consumer perceived value: quality value, pricing dynamics, emotional resonance, and social connections. Employing a descriptive research approach, we harnessed a robust sample of 200 respondents for each product category. Our findings unveil a compelling nexus between consumer perceived value and the elusive realm of consumer satisfaction. Notably, the paramount influence is wielded by the dimension of quality. Consequently, we implore companies to channel their efforts towards elevating product excellence, while judiciously attending to price dynamics, emotional resonance, and social affiliations to maximize consumer gratification.